Investigating Users' Perspectives of Coworking Space: Cases of Bangkok CBD - Sonthya Vanichvatana (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Coworking space has changed working style from traditional office space to a shared working environment with different natures of knowledge professionals and industry. This style of work space has been increasingly popular during the past decade in major cities across the globe including the central business district (CBD) of Bangkok, Thailand. Users can come from various ages and environments including: students, corporate remote workers, and independent workers/freelancers. The initial investment of this type of business is not complex. Hence, the survival of this type of business is not easily guaranteed because of not only high competitiveness but also unclear information from the user side. Entrepreneurs of coworking spaces need to understand the characteristics and perspectives of users which may differ in various regions and cultures. This research will investigate the users of coworking spaces who are independent workers about their demand behaviors and perspectives on the businesses' operations as essential factors in choosing a working space. The scope will cover users of coworking spaces in Bangkok CBD, Thailand. Research approach will apply quantitative analysis through questionnaire surveys during November, 2017. The research results will be beneficial to the entrepreneurs of coworking spaces to understand the needs of target users and to support their businesses investment strategic.
Keywords: 650; Coworking; Coworking space; Bangkok CBD; Entrepreneur; User perspective